2-Benzoyl-1H-benzimidazole - Ai, L.; Shen, Xiu-Min; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C14H10N2O, the benzoyl ring and benzimidazole ring system are aligned at a dihedral angle of 50.2 (2)degrees. In the crystal, intermolecular N-H center dot center dot center dot N hydrogen bonds between adjacent imidazole groups generate supramolecular C(4) chains running along the b axis.